Potential Neuroendoscopic Complications: An Anesthesiologist's Perspective - Haldar, Rudrashish (Asian J Neurosurg, 2019)
Endoscopic techniques are being used extensively used in the current times for the diagnosis and treatment of numerous intracranial pathologies. Although the morbidity associated with these procedures is lower as compared to other conventional surgical modalities, neuroendoscopic techniques have its own fair share of distinct complications such as bleeding, cerebrospinal fluid leakage, and subdural hematoma. However, certain specific complication fall within the purview of the attending anesthesiologist who should remain vigilant, anticipating these problems to occur and should be well equipped to deal with such contingencies. This review attempts to sensitize the anesthesiologists regarding the well-known as well as rare complications of intracranial neuroendoscopic procedures and to familiarize them with their diverse presentations, preventive strategies, and management protocols.